Representing Ebola : Culture, Law, and Public Discourse about the 2013-2015 West African Ebola Outbreak. - Hasian, Marouf A., Jr.; Hasian, Marouf A. (Blue Ridge Summit : Fairleigh Dickinson University Press, 2016)
Representing Ebola addresses the legal and cultural facets of the latest West African Ebola outbreak for both an academic and general audience.
Intro -- Contents -- Acknowledgments -- Chapter 1. Arguing about the Cultural and the Legal Meanings of the 2013-2015 West African Ebola Outbreak -- Chapter 2. NGO Organizational Tales, the Discovery of "Patient Zero," and MSF's Stories about the Origins of the 2013-2015 West African Ebola Outbreak -- Chapter 3. The Legal and Ethical Duties That Are Owed to "Contact Tracers" and Other West African Volunteers -- Chapter 4. The Saga of Kaci Hickox and the Nature, Scope, and Limits of Human Rights Discourses in Ebola Contexts -- Chapter 5. The IMF, the World Bank, and Debates about the Role of Political Economy in Ebola Outbreak Contexts -- Chapter 6. Anticipating the Ebola Apocalypse and American Mediascapes -- Chapter 7. Liberia's 2014 Autoimmunization of the West Point Suburb and the Return of the Colonial Cordon Sanitaire -- Chapter 8. Belated Military Humanitarianism and American "Ebola Exceptionalism" during the West African Ebola Outbreak -- Chapter 9. The Legal and Cultural Legacies of the 2013-2015 West African Outbreak -- Bibliography -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Africa, Western; Electronic books